PENGARUH ANGGARAN BIAYA OPERASIONAL, PRODUKSI DAN PENDAPATAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Susanti, Astri (Jurnal Gici Jurnal Keuangan dan Bisnis, 2024)
Therefore, this research aims to analyze operational, production and income budgets against Return on Assets (ROA) in Manufacturing Companies Listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. This research uses a quantitative approach using descriptive statistical analysis. The data source used in this research is secondary data in the form of annual published financial reports of Sub-Food and Beverage Manufacturing Companies listed on the IDX for the 2018-2022 period which are published and downloaded via the PT Bursa Efek Indonesia website. The data analysis technique uses multiple linear regression using SPSS. Hypothesis testing is carried out using the F-test, t-test and coefficient of determination. Meanwhile, the classical assumption tests used in this research are the normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. The results of this research show that the operational cost budget has a significant negative influence on Return On assets with a value of tcount (-2.830) > ttable 1,695, Production Costs have an insignificant influence on Return On assets with a value of tcount (1.840) > ttable 1,695, while income There is no significant influence on Return On Assets with a value of tcount (-0.984) < ttable 1,695. Simultaneous testing of the data results in operational costs, production and income having a significant influence on Return On Assets with a value of Fcount (4.342) > Ftable (2.90).